MAPPING SUSTAINABILITY RESEARCH: A MANAGEMENT CONTROL SYSTEMS PERSPECTIVE - Muhammad Ja'far Shodiq; Rita Rosalina (Ikatan Dosen Menulis, 2025)
This study aims to map the development of scientific literature on Sustainability in Management Control Systems perspective during the period 2020-2025, with a total of 396 articles originating from 214 internationally indexed Scopus journals using a bibliometric approach based on data from Scopus. MCS is a management control system designed to support the effective implementation of sustainability strategies, integrating economic, social, and environmental aspects into business practices. The bibliometric method was chosen to analyze publication trends, collaboration patterns between authors and institutions, and key research themes developing in this field. Data were collected through keyword searches related to MCS and analysed using Bibliometric software in R Studio. The results of the analysis revealed that, although MCS publication productivity has shown fluctuations with a downward trend in recent years, academic interest in this topic remains high, with a significant average citation count. Countries such as China, Australia, and Indonesia are the main contributors to this study, with the level of international collaboration continuing to increase. Keyword findings and thematic maps show the primary focus of research on the relationship between management accounting, management control systems, environmental management, and sustainable development. In addition, issues such as emission control, risk management, and corporate governance are also essential parts of academic discourse related to MCS. This study contributes to clarifying the development trend of MCS science and identifying central themes and potential future research directions. The practical implications of this study can be a reference for companies and policymakers in designing more effective and sustainable control systems. This study also encourages further research development by expanding the database and integrating qualitative approaches to understand MCS implementation in a contextual context.